Simmel’s Philosophy of Life and Somaesthetics: A Conversation with Richard Shusterman - Marino, Stefano (Simmel Studies, 2025)
In this conversation, Stefano Marino engages Richard Shusterman in a wide-ranging dialogue on the contemporary philosophical significance of Georg Simmel. Drawing on Shusterman’s recent work on the relationship between Simmel, pragmatism, and somaesthetics, the interview reassesses Simmel’s place within twentieth- and twenty-first-century philosophy, moving beyond his conventional reception as primarily a sociologist. Through Marino’s carefully structured questions, the discussion explores the intersections between Simmel’s philosophy of life and somaesthetics, focusing on embodiment, sensory experience, self-cultivation, fashion, culture, and the art of living. At the same time, the dialogue highlights important theoretical divergences, particularly concerning the role of the body, the senses, and the relation between subjective and objective culture. The interview also addresses broader issues, including Simmel’s philosophical reception in the Anglo-American world, his complex relationship with pragmatism, and the significance of his Jewish background for understanding concepts such as distance, identity, and the stranger. Rather than presenting Simmel simply as a precursor of contemporary thought, the conversation offers a nuanced philosophical engagement that underscores both the enduring relevance and the unresolved tensions of his work for current debates in aesthetics, social philosophy, and theories of embodiment.